Формування конкурентних переваг продукції промислових підприємств - Ковальов, Євген Володимирович; Давидюк, Тетяна Вікторівна; Колотюк, Олена Іванівна; Перерва, Петро Григорович (НТУ "ХПІ", 2016)
У статті розглянуто питання створення механізму формування та оцінки конкурентних переваг промислового підприємства. Завданням статті є розробка пропозицій щодо моделювання конкурентної переваги, прогнозування зміни сили конкурентної переваги за етапам и його життєвого циклу.

In the article the question of creation of the mechanism of formation and evaluation of competitive advantages of the industrial enterprise. The objective of this article is to develop proposals for modeling competitive advantage forecasting power change competitive advantages in stages of its life cycle.
The formation of competitive advantages of products of industrial enterprises
Keywords: ринок; конкуренція; маркетингова політика; ринкові відносини; market; competition